Pengetahuan Ibu Hamil tentang Hepatitis B di Puskesmas Mojoagung Kabupaten Jombang - wijayati, wahyu (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
The transmission of hepatitis B from mother to child has a probability of around 90%. One of the factors that influences efforts to prevent hepatitis B transmission is knowledge about hepatitis B. The aim of this research is to determine the knowledge of pregnant women about hepatitis B at the Mojoagung Community Health Center, Kediri Regency. This research is a descriptive study with the variable studied being pregnant women's knowledge about Hepatitis B. The population in the study was all pregnant women at the Mojoagung Community Health Center from 12 to 17 February 2024, totaling 691 pregnant women. The sampling technique used is Accidental Sampling. The samples obtained were 50 pregnant women. The instrument used in collecting primary data is a questionnaire, the data is processed and presented as a percentage. The results showed that the knowledge of pregnant women about hepatitis B was in the poor knowledge category of 28 pregnant women (56%), the sufficient knowledge category was 9 pregnant women (18%), and the good knowledge category was 13 pregnant women (26%) of the total respondents. 50 pregnant women. Pregnant women's knowledge about hepatitis B is important, as one of the capital in successful efforts to prevent the occurrence of hepatitis B in mothers and babies, it is necessary to take steps or methods in providing education about hepatitis B which leads to an understanding of hepatitis which has a positive impact, namely on mothers. Pregnant women can have regular check-ups.